Editorial: Emerging Technologies and Innovation for Digital Economy and Transformation - Jallouli, Rim; Bach Tobji, Mohamed Anis; Soares, Ana Maria; Casais, Beatriz; Belkhir, Meriam (Journal of Telecommunications and the Digital Economy, 2024)
This editorial is organized into three parts, providing a panoramic understanding of the multifaceted dimensions of digital economy and transformation. It opens with an introduction discussing the dynamic changes within the digital economy, highlighting the pivotal role of technologies and innovation as driving forces for the digital economy and transformation. It then offers insights into the selected papers and highlights the main themes explored. The third section underscores the significance of digital technologies and innovation, emphasizing their emergence as a burgeoning multidisciplinary research field. The editorial concludes by emphasizing the importance of recognizing diversity in digital transformation, and expressing gratitude to the primary contributors who shaped this special issue.